Credit discount definition

Answers

Answer 1
Answer: Hi There! :)

Credit discount definition?

to leave out of account as being unreliable, prejudiced, or irrelevant  

Related Questions

Is 1 prime, composite, or neither? prime composite neither
Suppose S and T are mutually exclusive events. Find P(S or T). P(S) = 20%, P(T) = 22%
imagine an investigation in which 40 students were asked to determine their chronotype by choosing from among four chronotypes instead of three: morning person, night person, neither, or both. If there is no relationship between chronotype and birth month, about what fraction of the students would you expect to pick the chronotype that matches their birth month? why do you think this?
Use the elimination method1) 3x+y=-1 5x-y=92) 4x+6y=24 4x-y=103)2x-y=-3 x+3y=164) 2x+3y=7 3x+4y=10
5 + 3 + 52 × 5 − 2 =

the sears tower in chicago is 1450 feet high. A model of the tower is 24 inches tall. What is the ratio of the height of the model to the height of the actual sears tower?

Answers

24 : 1450
model : sears tower
I hope I helped! ;)

When two musical notes are a “sixth” apart, the frequency of the lower note is 3/5 the frequency of the higher note. Using f as the frequency of the higher note, write an expression for the frequency of the lower note. HELP!1. f - 2/5

2. 3/5 f

3. 2/5 f

4. 3/5 + f

Answers

The correct expression for the frequency of the lower note when two musical notes are a sixth apart is: 3/5 f

Given that two musical notes are a “sixth” apart, the frequency of the lower note is 3/5 the frequency of the higher note.

We need to determine the expression for the frequency of the lower note.

When two musical notes are a "sixth" apart, it means that there are five whole steps or intervals between the two notes.

In music theory, each whole step corresponds to multiplying the frequency by a constant factor.

If we denote the frequency of the higher note as f, then the frequency of the lower note, which is 3/5 times the frequency of the higher note, can be calculated by multiplying f by 3/5.

Therefore, the correct expression for the frequency of the lower note is 3/5 f.

Learn more about musical notes click;

brainly.com/question/31825973

#SPJ4

Answer:

2. 3/5 f

Step-by-step explanation:

the lower note is the product of it's fractional part and the frequency of the higher note.

The first square number is 1, and the sum of the first 20 square numbers is 2870. Work out the sum of the first 21 square numbers.

Answers

If the sum of the first 20 square numbers is 2870  then sum of the first 21 square numbers is 3311.

What is Sequence?

Sequence is an enumerated collection of objects in which repetitions are allowed and order matters.

The first square number is 1, and the sum of the first 20 square numbers is 2870.

We need to find the  sum of the first 21 square numbers.

for first 20 numbers  the answer is

n(n+1)(2n+1)/6

20*21*41/6 = 2870

Now we have to find the sum of first 21 square numbers.

21²=441

Now add it with 2870

2870+441=3311

Hence,  the sum of the first 21 square numbers is 3311.

To learn more on Sequence click:

brainly.com/question/21961097

#SPJ2

The 21st square number is 21^2 = 441
2870 + 441 = 3311

Find the non-extraneous solutions of the square root of the quantity x plus 9 minus 5 equals quantity x plus 4.

Answers

( x+9) - 5= ( x+4 ) Try this it should help you ^^

please help me :Tom ate four more pieces of fruit than Janet. Sylvia ate twice as many pieces of fruit as Tom. If x represents the number of pieces of fruit that Janet ate, write an expression to represent the amount of fruit that Sylvia ate.

Answers

J=X
T= X+4
S= 2(X+4). So s is sylvia

Final answer:

If x represents the number of pieces of fruit Janet ate, then Sylvia ate 2 * (x+4) pieces of fruit based on the given question.

Explanation:

The question requires an algebraic expression to show how many pieces of fruit Sylvia ate. According to the question, Tom ate four more pieces of fruit than Janet. If x is the number of fruits Janet ate, then we can represent the number of fruits Tom ate as x + 4.

Next, the question states that Sylvia ate twice as many pieces of fruit as Tom. So, we can represent the number of pieces of fruit Sylvia ate as 2 * (x+4). Hence, this is the expression that represents the amount of fruit that Sylvia ate.

Learn more about Algebraic Expression here:

brainly.com/question/953809

#SPJ2

Explain the derivation behind the derivative of sin(x) i.e. prove f'(sin(x)) = cos(x)How about cos(x) and tan(x)?

Answers

1.

f'(\sin x) =  \lim_(h \to 0)  (f(x+h) - f(x))/(h)  =    \lim_(h \to 0)  (\sin(x+h) - \sin(x))/(h)  =  \n  \n  =   \lim_(h \to 0)  (2 \sin( (x+h - x)/(2)) \cdot \cos( (x+h+x)/(2))  )/(h) =   \lim_(h \to 0)    (2 \sin( (h)/(2)) \cos( (2x+h)/(2) ) )/(h)   =  \n  \n   = \lim_(h \to 0)     [ (\sin( (h)/(2)) )/( (h)/(2) )  \cdot  \cos ((2x+h)/(2)) ] =   \lim_(h \to 0) [1 \cdot \cos( (2x+h)/(2) )  ] =

= \cos( (2x)/(2)) = \boxed{\cos x}

2.

f'(\cos x) =  \lim_(h \to 0) (f(x+h) - f(x))/(h) =   \lim_(h \to 0)  (\cos(x+h) - \cos(x))/(h)  =  \n  \n  =   \lim_(h \to 0)  (-2 \sin ( (x+h+x)/(2)) \cdot \sin ( (x+h-x)/(2))  )/(h)  =   \lim_(h \to 0)  (-2 \sin ( (2x+h)/(2)) \cdot \sin ( (h)/(2))  )/(h)  =  \n  \n  =     \lim_(h \to 0)   (-2 \sin ( (2x+h)/(2)) )/(2)     \cdot  (sin( (h)/(2)) )/( (h)/(2) )    =   \lim_(h \to 0)  -\sin( (2x+h)/(2)) \cdot 1 =

= -\sin(  (2x)/(2)) = \boxed{\sin x }

3.

f'(\tan) = \lim_(h \to 0) (f(x+h) - f(x))/(h) = \lim_(h \to 0) (\tan(x+h) - \tan(x))/(h) = \n \n = \lim_(h \to 0) ( (\sin(x+h-x))/(\cos(x+h) \cdot \cos(x)) )/(h) = \lim_(h \to 0) ( (\sin(h))/( (\cos(x+h-x) + \cos(x+h+x))/(2) ) )/(h) =

= \lim_(h \to 0) ( (\sin(h))/(\cos(h) + \cos(2x+h)) )/( (1)/(2)h ) = \lim_(h \to 0) (\sin(h))/( (1)/(2)h \cdot [\cos(h) + \cos(2x+h)] ) = \n \n = \lim_(h \to 0) (\sin(h))/(h) \cdot (1)/( (1)/(2) \cdot (\cos(h) + cos(2x+h) ) = 1 \cdot (1)/( (1)/(2) \cdot (1+ cos(2x) ) = (2)/(1 + 2 \cos^(2) - 1 ) = \n \n = (2)/(2 \cos^(2) x) = \boxed{ (1)/(\cos^(2)x) }

4.

f'(\cot) = \lim_(h \to 0) (f(x+h) - f(x))/(h) = \lim_(h \to 0) (\cot(x+h) - \cot(x))/(h) = \n \n = \lim_(h \to 0) ( (\sin(x - x - h))/(\sin (x+h) \cdot \sin (h)) )/(h) = \lim_(h \to 0) ( (\sin(-h) )/( (\cos(x+h-x) - \cos(x+h+x))/(2) ) )/(h) =

= \lim_(h \to 0) ( (-\sin(h))/(\cos(h) - \cos(2x+h)) )/( (1)/(2)h ) = \lim_(h \to 0) ( - \sin(h))/( (1)/(2)h \cdot [\cos(h) - \cos(2x+h)] ) = \n \n = \lim_(h \to 0) (- \sin (h))/(h) \cdot   (1)/( (1)/(2) \cdot [\cos(h) - \cos(2x+h)] )  = -1 \cdot  (2)/(1 - cos(2x))  =  \n  \n  = - (2)/(1 -1 + 2 \sin^(2)x)  = - (2)/(2 \sin^(2) x) = \boxed{- (1)/(\sin^(2) x) }
I posted an image instead.